The Influence of Brand Equity and Product Innovation on Purchase Intention with Competitive Advantage as a Mediator: A Study on Mie Sedaap Consumers in Garut - Fourinta, Ananda; Supriyadi, Didit; Setiawan , Rahyuniati (Manunggal Halim Jaya, 2026)
This study aims to examine how brand equity and product innovation influence purchase intention, with competitive advantage acting as a mediating variable among Mie Sedaap consumers in Garut Regency. The research employs an explanatory survey with 400 respondents, and the data are analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 4 software. The findings reveal that both brand equity and product innovation have a positive and significant impact on purchase intention, both directly and indirectly through competitive advantage. This suggests that gaining a competitive advantage is crucial in enhancing the effects of brand strategy and product innovation on consumer purchasing decisions. The study's results imply that companies should focus on maintaining and improving brand equity, conducting product innovations aligned with market trends, and strengthening differentiation strategies to sustain competitive positions and boost consumer purchasing interest.